The Effect of Brand Credibility, Brand Image and Customer Satisfaction on Behavioural Intentions in Traditional Medicine Market - Oppong, Peter Kwasi (Journal of Social and Development Sciences, 2021)
Brands with stronger image, credibility, and greater customer satisfaction engender favourable behavioural intentions, which serves as an essential competitive weapon in a market. The impact of brand image, credibility, and satisfaction on behavioural intentions are well-documented in the literature. There is, however, little or no research on the influence of credibility and image on behavioural intentions through the intervening role of satisfaction in the traditional medicine market. As a result, the research aimed to assess the intervening role of customer satisfaction in the effect of brand image and credibility on behavioural intentions in the traditional medicine market. Data were distributed to a sample of 265 customers via a systematic sampling strategy. The hypotheses formulated were tested by using covariance-based structural equation modelling. The research confirmed that satisfaction perfectly mediated the effect of credibility on customers’ behavioural intentions in the traditional medicine market. However, no mediational relationship between the brand image and behavioural intentions was established. Consequently, this study contributes to the brand theory by displaying the mediated role of customer satisfaction in the impact of brand credibility on the customers’ behavioural intentions, particularly in the traditional medicine market. As an emerging industry, this paper also advances the practitioners’ knowledge about how to build and manage credibility, satisfaction, and image to strengthen the customers’ behavioural intentions in the traditional medicine market.